KARAKTERISTIK TARI BEDHAYAN CHENG HO KARYA SANGGHITA ANJALI: STUDI TENTANG INOVASI BERSUMBER TARI TRADISI - Febika Fahrinisa; Sriyadi (TAMUMATRA, 2025)
Bedhayan Cheng Ho Dance, a work by Sangghita Anjali from Semarang, portrays the story of Admiral Cheng Ho, a Chinese explorer who played a significant role in the historical cultural interactions between China and the Nusantara, particularly in Semarang. The harmony between Javanese and Chinese cultures is reflected in its presentation, making it a representation of cultural acculturation in the region. This article aims to describe the characteristics of Bedhayan Cheng Ho Dance as an innovation rooted in traditional dance, particularly the Bedhaya court dance. This study employs a qualitative research method with a choreological approach. The findings indicate that innovations in this dance create a cultural expression that embodies the synthesis of Javanese and Chinese elements, serving as the choreographer’s response to the local cultural context. Beyond its artistic exploration, Bedhayan Cheng Ho Dance also represents the dynamics of cultural acculturation in Semarang. The fusion of Javanese and Chinese cultural elements serves as the defining characteristic of this dance, emerging from the choreographer’s innovation in adapting and developing the Bedhaya tradition. Structurally, the dance integrates movements from wushu martial arts with the foundational movements of Javanese dance, particularly the Surakarta style. Its composition emphasizes arm movements, legwork, and dynamic torso gestures, embodying the aesthetic synthesis of both cultures.